STRATEGI PBL-GREEN UNTUK MENINGKATKAN LITERASI SAINS, KETERAMPILAN METAKOGNITIF, DAN SIKAP PEDULI LINGKUNGAN PESERTA DIDIK DALAM PEMBELAJARAN BIOLOGI - Kadir, St. Fatima; Muarifah, Muarifah; Muhiddin Palennari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Biology learning in the 21st century faces challenges in enhancing students’ scientific literacy, metacognitive skills, and environmental awareness. Problem-Based Learning (PBL) and the Reading-Questioning-Answering (RQA) strategy have proven effective in empowering cognitive and metacognitive abilities; however, they have not explicitly integrated environmental education and ecolo-gical character formation. This article aims to synthesize relevant literature and introduce an innovative strategy called PBL-GREEN as an extension of PBL-RQA. The method employed is a literature study analyzing national and international journals and books related to PBL, RQA, scientific literacy, metacognition, and environmental education. PBL-GREEN integrates five key stages: Guided Rea-ding, Raising Questions-Answering, Exploring Problems, Environmental Action, and Nurturing Attitudes. This strategy has the potential to enhance scientific literacy through guided scientific reading, foster metacognitive skills through ques-tioning and reflection, and cultivate environmental care through real actions and ecological character development. Therefore, PBL-GREEN offers an integrative approach that connects knowledge, skills, and environment-based learning.